2020
DOI: 10.3390/cosmetics7020039
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of Jeju Wax Apple (Syzygium samarangense) and Safety of Human Keratinocytes and Primary Skin Irritation Test

Abstract: This study analyzed the antioxidant activity, cell viability, and human skin primary irritation test using the hot-water extracts of the Syzygium samarangense. As a result of the recent warmer climate, tropical plants have flourished on Jeju Island, and S. samarangense is one of these plants known to have biological activities. In this study, the hot-water extract of S. samarangense leaf and branch was analyzed. Antioxidant activity was measured by DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS (2,2′-azino-bis(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Primary skin irritation responses were assessed according to the PCPC guidelines. The reaction results for each test substance were calculated from the formula shown below [ 50 , 51 ]. The study was approved by the Industrial Review Board (IRB) of Dermapro Inc. and was conducted in accordance with the Helsinki Declaration as a declaration of the ethical principles for medical research after obtaining written consent from each volunteer (IRB number: 1-220777-A-N-01-DICN22080).…”
Section: Methodsmentioning
confidence: 99%
“…Primary skin irritation responses were assessed according to the PCPC guidelines. The reaction results for each test substance were calculated from the formula shown below [ 50 , 51 ]. The study was approved by the Industrial Review Board (IRB) of Dermapro Inc. and was conducted in accordance with the Helsinki Declaration as a declaration of the ethical principles for medical research after obtaining written consent from each volunteer (IRB number: 1-220777-A-N-01-DICN22080).…”
Section: Methodsmentioning
confidence: 99%
“…In the previous research, results showed that hot water branches extract of java apple (Syzygium samarangense) had an absorbance of 4.8 at 1000 µg/mL and hot water leaves extract of java apple has an absorbance of 4.1 at 1000 µg/mL, lower compared to L-ascorbic acid that had an absorbance of 4.2 at 100 µg/mL, according to CUPRAC method [21]. In the present research, antioxidant activities of green honey deli water apple leaves range from 10.79 to 221.47 mg AAE/g, branches range from 10.46 to 222.51 mg AAE/g, and fruits range from 19.45 to 25.04 mg AAE/g, according to CUPRAC method.…”
Section: Cuprac Methods Measures Antioxidant Activities Based On the ...mentioning
confidence: 99%
“…The primary skin irritation response was evaluated in accordance with the PCPC guidelines. The skin reaction results for each test substance were calculated from the formula shown below [ 33 , 34 ]. This study was approved by the Institutional Review Board (IRB) of Dermapro Inc. and conducted according to the Declaration of Helsinki as a statement of ethical principles for medical research after obtaining written informed consent from each volunteer (IRB no.…”
Section: Methodsmentioning
confidence: 99%